EVALUATION OF PLASMA TRACE ELEMENTS LEVELS IN HUMAN IMMUNODEFICIENCY VIRUS (HIV) PATIENTS ON HIGHLY ACTIVE ANTIRETROVIRAL THERAPY (HAART) ATTENDING FEDERAL MEDICAL CENTER OWERRI, IMO STATE - Ejiofor, D. Chinedu; Edward-Ejiofor, B.; Alisi, P. Ngozi; Raymond, A. Ude; Earnest, N. Emeka; Amah, C. Ifeanyi; Obi, A. Uche; Samson, A. (FUDMA JOURNAL OF SCIENCES, 2025)
Trace elements play significant biological roles that drive life and can be affected by the deleterious effects of the Human Immunodeficiency Virus (HIV). Highly active antiretroviral therapy (HAART) is a combination of several antiretroviral therapies that have the potential to improve the quality of life of individuals with HIV infection. The aim of this study was to evaluate the plasma trace elements of HIV-positive individuals on HAART. A total of 196 participants were recruited for the study, including 126 HIV patients on HAART, 35 HIV non-HAART patients, and 35 HIV-negative subjects. HIV status and plasma trace element levels of the participants were determined using standard procedures. The results of the study showed that zinc, selenium, and iron levels in HAART patients were significantly higher (p<0.05) than those in non-HAART patients (control group 1) but lower than those in the control group 2. Additionally, these elements were significantly higher (p<0.05) in male patients on HAART compared to their female counterparts. In conclusion, this study suggests that HAART has a positive influence on blood serum trace element metabolism in HIV-positive patients.